Continuing rise of Type 2 diabetes incidence in children and young people in the UK. Issue 6 (24th March 2018) - Candler, T. P.; Mahmoud, O.; Lynn, R. M.; Majbar, A. A.; Barrett, T. G.; Shield, J. P. H.
Abstract: Aims: To estimate the incidence of Type 2 diabetes in children aged <17 years, compare this with similar data 10 years ago, and characterize clinical features at diagnosis in the UK and Republic of Ireland. Methods: Using the British Paediatric Surveillance Unit reporting framework, cases of Type 2 diabetes diagnosed in children aged <17 years between 1 April 2015 and 30 April 2016 were reported each month. Results: A total of 106 cases were reported, giving a UK incidence of 0.72/100 000 (95% CI 0.58–0.88). Children from ethnic minorities had significantly higher incidence compared with white children (0.44/100 000) with rates of 2.92/100 000 and 1.67/100 000, in Asian and BACBB (black/African/Caribbean/black British) children respectively. Sixty‐seven percent were girls and 81% had a family history of Type 2 diabetes. The mean BMIsd score at diagnosis was 2.89 (2.88, girls; 2.92, boys); 81% were obese. Children of Asian ethnicity had a significantly lower BMIsd score compared with white children ( P <0.001). There was a trend in increased incidence from 2005 to 2015, with a rate ratio of 1.35 (95% CI 0.99–1.84), although this was not statistically significant ( P =0.062). There was statistical evidence of increased incidence among girls ( P =0.03) and children of South‐Asian ethnicity ( P =0.01) when comparing the 2005 and 2015 surveys. Conclusions: Type 2 diabetes remains far less common than Type 1 diabetes in childhood in the UK, but the number of cases continues to rise, with significantly increased incidence among girls and South‐Asian children over a decade. Female gender, family history, non‐white ethnicity and obesity were found to be strongly associated with the condition. What's new?: The 2015/2016 UK incidence of Type 2 diabetes in children aged <17 years was 0.72 per 100 000 per year The incidence of Type 2 diabetes amongst girls and South‐Asian children has risen significantly over the last decade. Female gender, family history, non‐white ethnicity and obesity were strongly associated with Type 2 diabetes in childhood. Comorbidities are commonly identified at diagnosis, including 37% with non‐alcoholic fatty liver disease and 21% with hypertension The most common presenting complaint at diagnosis after osmotic symptoms (polyuria, polydipsia and weight loss) was recurrent, mainly genital, infections, although over a third of cases were asymptomatic and detected on obesity screening investigations